FLOTAC Technique for Soil-Transmitted Helminth Infection Diagnosis - Helena Ullyartha Pangaribuan; Taniawati Supali; Heri Wibowo (Faculty of Medicine, Universitas Padjadjaran, 2021)
Human helmintiasis is a neglected disease with significant economic impacts caused by its effects on performance and cognition. The burden of many helminth infections is not well understood due to the lack of progress in detecting low-intensity infection in elimination programs. Furthermore, the decision for individual and community treatments, as well as the community-based control program evaluation, obviously depends on the technics used for parasitological diagnostic. A well-established diagnostic technic will be beneficial to detect and eliminate the disease. Therefore, this study aimed to compare the performance of FLOTAC and FECT technics for detecting helminth infections in human stool. A total of 149 fecal specimens were collected from schoolchildren in Nangapanda village, Ende District, East Nusa Tenggara Province in 2012. The sensitivity of both technics was analyzed using the kappa analysis. Positive results from both technics were used as the gold standard. The sensitivity of FLOTAC for diagnosing T. Trichiura, A. lumbricoides and hookworm infections were 100%, 100%, and 82%, respectively, while the sensitivity of FECT was 80%, 7%, and 18%, respectively. FLOTAC yielded considerably higher mean faecal egg counts (11,452, 1,038, and 19 eggs per gram stool (EPG) for A. lumbricoides, T. Trichiura, and hookworm). FLOTAC technique was considerably more sensitive than FECT in diagnosing soil-transmitted helminth infections. In conclusion, FLOTAC can be used as a diagnosis tool for future helminth control programs.